Filipino college students' mental health literacy - Ines, Jennifer V. (Animo Repository, 2016)
Mental Health Literacy of 797 first year Filipino college students from De La Salle University was examined. Results show that 55.2% of the sample was able to recognize depression in a given vignette using the correct label and 95. 7% of students expressed intention to seek help from different sources such as family (58.5%), friends (48.8%), counselor (38. I%), etc., if they experienced the same problem as the character in the story. Filipino college students attributed depression to what professionals would commonly describe as triggers such as day-to-day problems, childhood problems, and guilt over wrongful acts, trauma, etc. Counselors, family, friends, psychologists and psychiatrists Were viewed as helpful resources to people who suffer from depression. Social workers, nurses and helplines were among the least nominated by the participants. Preferences over non-prescribed products such as tea, organic medicines and vitamins rather than prescribed medications such as antidepressants and anti-psychotics were apparent. Counseling was nominated by most college students to be helpful for a depressed individual. Lastly avoiding stress was viewed as an effective preventive strategy which is contrary to what professionals recommend. Differences between participants personal and perceived stigma were also found in the study. Implications of such to proper intervention for mental illness and importance of improving mental health literacy among Filipino college students are discussed.